Witches’ Tears: Spiritual Feminism, Epistemology, and Witch Hunt Horror Stories - Zwissler, Laurel (Pomegranate, 2016)
Contemporary Pagans have historically been invested in the idea of Paganism’s survival from pre-Christian times through the early modern witchcraft trials to the present, but the story takes on specifically gendered significance within spiritual feminism. The “Burning Times” complex of ideas combines stories of horrific and often sexualized torture with assertions that the true religion of persecuted Witches was not only Pagan, but traces back to Neolithic, Goddess-centered matriarchy. Foundational spiritual feminists Mary Daly, Zsuzsanna Budapest, and Starhawk, as well as first-wave author Matilda Joslyn Gage, have put horror stories of the witch hunts in their publications, each deriving different feminist mandates from these shared tales of torture. I also take this opportunity to reflect on some of my own experiences as a scholar and feminist engaged with the moral weight of witchcraft history.